Cervical spine signs and symptoms: perpetuating rather than predisposing factors for temporomandibular disorders in women - Débora Bevilaqua-Grossi; Thaís Cristina Chaves; Anamaria Siriani de Oliveira (University of São Paulo, 2007)
AIM: The purpose of this study was to assess in a sample of female community cases the relationship between the increase of percentage of cervical signs and symptoms and the severity of temporomandibular disorders (TMD) and vice-versa. MATERIAL AND METHODS: One hundred women (aged 18-26 years) clinically diagnosed with TMD signs and symptoms and cervical spine disorders were randomly selected from a sample of college students. RESULTS: 43% of the volunteers demonstrated the same severity for TMD and cervical spine disorders (CSD). The increase in TMD signs and symptoms was accompanied by increase in CSD severity, except for pain during palpation of posterior temporal muscle, more frequently observed in the severe CSD group. However, increase in pain during cervical extension, sounds during cervical lateral flexion, and tenderness to palpation of upper fibers of trapezius and suboccipital muscles were observed in association with the progression of TMD severity. CONCLUSION: The increase in cervical symptomatology seems to accompany TMD severity; nonetheless, the inverse was not verified. Such results suggest that cervical spine signs and symptoms could be better recognized as perpetuating rather than predisposing factors for TMD.